THE EFFECT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE ON BEHAVIORAL INTENTION TO USE THROUGH THE INTERVENING ATTITUDE TOWARD USING VARIABLES IN THE STUDY OF SHOPEEPAY E-WALLET SERVICES (Case study on ShopeePay Users in Yogyakarta) - Ida Bagus Nyoman Udayana; Agus Dwi Cahya; Fadhilla Ajeng Aqdella (STKIP Singkawang, 2022)
This research was conducted with the aim of identifying and analyzing user attitudes and user intentions towards e-wallet service users on ShopeePay. With several related variables in this study, namely perceived usefulness, perceived ease of use, behavioral intention as the dependent variable and attitude toward using as the intervening variable. The population in this study are ShopeePay service users, with a sample of 100 ShopeePay users as respondents. Data was collected using the questionnaire method. The test results in this study are perceived usefulness has a positive effect on behavioral intention, perceived ease of use has a positive effect on behavioral intention, attitude toward using has a positive effect on behavioral intention.